FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN MANUFAKTUR TERDAFTAR DI BEI MELAKUKAN PERGANTIAN AUDITOR SECARA VOLUNTARY - Pradipta, Randi Pujas; Septiani, Aditya (Diponegoro Journal of Accounting, 2014)
This research aimed to test the influence of audit opinion, changes in management, size of the client, complexity, client firm’s growth on the voluntary auditor switching. The voluntary auditor switching would perform many problems, because it was happen in out of regulation that has been taken. Data collecting in this research used a purposive sampling of Manufacture Company that was registered on the Indonesia Stock Exchange (BEI) in 2010 until 2012. This research used 31 manufacture companies that were used as sample firms. Logistic regression in this research was used to test the hypothesis. The results of this research showed that the independent variables that influenced the voluntary auditor switching was the change in management. Besides that, the other independent variables that weren’t influence on the voluntary auditor switching were the audit opinion, the size of client, the complexity and the client firm’s growth.